New Genus and Species of Spiders of the Subfamily Zodariinae (Araneae, Zodariidae) from Pakistan - Ovtchinnikov, S.V. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2006)
Indozodion inayatullahi Ovtchinnikov, gen. et sp. n. from Pakistan is described. The spider family Zodariidae is recorded from Pakistan for the first time. Описан Indozodion inayatullahi Ovtchinnikov, gen. et sp. n. из Исламабада. Пауки из семейства Zodariidae в Пакистане отмечены впервые.